The Phenomenon of Impulsive Buying Behavior on Ecommerce Twin Date Promotion : (Studying in the Island Communities: Bengkalis Island) - Rosa, Nageeta Tara; Amelia, Amelia; Domos, Erma; Alrasyid, Harun (Politeknik Negeri Bengkalis, 2024)
Bengkalis Island, based on its geographical circumstances, bordered by the Malacca Strait, Malaysia, from theEast, North, and West, can only be accessed via sea routes which are ro-ro transportation and ferries for the access,moreover, its citizens face challenges, especially in shopping, due to limited access to various goods. In such circumstances,e-commerce platforms like Shopee become crucial. One of its marketing strategies was a Twin Date Festival which canstimulate impulsive purchasing tendencies. Hence, this investigation seeks to find a potential association between Shopee'sTwin Date Festival and Impulsive Buying Behaviour, specifically among the Bengkalis Island Citizens. This study employsquantitative analysis techniques, utilizing the SPSS version 29 software for computations. The methodology encompassesthe distribution of questionnaires alongside observational and documentary methods. A sample of 150 respondents receivedthe questionnaires. Findings indicate a significant correlation between Shopee's Twin Date Festival and Impulsive Buyingbehaviors among Island Communities in the Bengkalis District, supported by a significance value of 0.001 <0.05 and aPearson correlation coefficient of 0.554, indicating a moderate relationship strength between the two variables. The positivecorrelation suggests that increased occurrences of Shopee's Twin Date Festival are associated with heightened impulsivebuying tendencies among Island Citizens in the Bengkalis District.